2018
DOI: 10.1186/s12955-018-0989-5
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of quality of life among Malaysian cancer patients: a cross-sectional study

Abstract: BackgroundCancer is a serious public health problem not only in Malaysia, also worldwide. The aim of this study was to determine the determinants of quality of life (QOL) among cancer patients in Peninsular Malaysia.MethodsA cross sectional study was conducted among 2120 cancer patients in Peninsular Malaysia, between April 2016 to January 2017. All cancer patients aged 18 years old and above, Malaysian citizens and undergoing cancer treatment at government hospitals were approached to participate in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 56 publications
5
23
0
Order By: Relevance
“…The results showed that fatigue showed a moderate correlation with reduced overall QOL. This finding is similar to that of a recent study done in Malaysia in 2018 [ 30 ] and several studies conducted globally, which reported significant negative relationships between QOL and fatigue [ 38 , 42 50 ]. The majority of cancer patients reported that fatigue prevented them from engaging in their normal daily routine and partaking in social activities such as spending time with friends or going to a restaurant [ 51 ].…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that fatigue showed a moderate correlation with reduced overall QOL. This finding is similar to that of a recent study done in Malaysia in 2018 [ 30 ] and several studies conducted globally, which reported significant negative relationships between QOL and fatigue [ 38 , 42 50 ]. The majority of cancer patients reported that fatigue prevented them from engaging in their normal daily routine and partaking in social activities such as spending time with friends or going to a restaurant [ 51 ].…”
Section: Discussionsupporting
confidence: 92%
“…The present results are consistent with those of Akhtari-Zavare M et al who also analyzed the association between the presence of nausea and QOL in cancer patients using the WHOQOL-BREF, and showed that nausea negatively influenced QOL in each component of physical, psychological, environmental and social relationships [ 30 ]. The present study also suggested that nausea caused by FOLFORINOX, a highly emetogenic risk regimen, and GnP therapy, a moderately emetogenic risk regimen, may affect QOL.…”
Section: Discussionsupporting
confidence: 92%
“…Compared with the literature on the QoL of the general population and chronic disease groups, literature on the QoL of detained offending groups is modest, albeit increasing (van Nieuwenhuizen, Schene, & Koeter, 2009). In a large cross-sectional study of prisoners, psychological distress was the strongest correlate of poor QoL (Muller & Bukten, 2019), and this relationship is consistently reported among both the general population (Caron, Cargo, Daniel, & Liu, 2019;Solis & Lotufo-Neto, 2019) and people with chronic diseases (Akhtari-Zavare et al, 2018;Björkman & Hansson, 2002;Fleury et al, 2013;Hansson & Björkman, 2007;Lehto, Ojanen, & Kellokumpu-Lehtinen, 2005;Rabin, Heldt, Hirakata, & Fleck, 2008). Poor QoL has also been reported among populations with similar risk patterns as detained offenders, such as people with histories of childhood maltreatment (Greger, Myhre, Lydersen, & Jozefiak, 2016), personality disorders (Cramer, Torgersen, & Kringlen, 2006;Lindstedt, Soderlund, Stalenheim, & Sjoden, 2005), and substance use disorders (De Maeyer, Vanderplasschen, & Broekaert, 2010;Muller, Skurtveit, & Clausen, 2016;Strada et al, 2017).…”
Section: Factors Related To Qol Among Offending Groupsmentioning
confidence: 96%